THE SIGNIFICANCE OF ORAL CREATION OF THE PEOPLE IN THE FORMATION OF NATIONAL VALUES - Akhmedova Gulchekhra Uskinovna (Journal of Learning on History and Social Sciences, 2024)
In this article, the role and importance of the art of bakshiki in the further strengthening and development of the national spiritual values of the Uzbek people, which have been formed over the centuries, are discussed. Also, for almost a century, various opinions have been expressed about the Alpomish saga. In them, various aspects of the epic are thoroughly researched. The issues of the importance of the large-scale reforms implemented in the further development of the wide promotion of folk art have been scientifically analyzed.